2022
DOI: 10.1177/20503121221104442
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled hypertension and associated factors among adult hypertensive patients on follow-up at public hospitals, Eastern Ethiopia: A multicenter study

Abstract: Objective: The aim of this study was to assess the magnitude of uncontrolled hypertension and associated factors among adult hypertensive patients on follow-up at public hospitals in Eastern Ethiopia. Methods: A hospital-based cross-sectional study was conducted among 415 hypertensive patients in Eastern Ethiopia from June 15 to July 15, 2021. A systematic random sampling technique was used to select the study participants. Data were collected through face-to-face interviews and reviewing patients’ charts. Biv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 64 publications
(90 reference statements)
0
15
1
Order By: Relevance
“…The prevalence of uncontrolled hypertension among patients with early CKD in our study was 58.3%, this is lower than ndings from other studies which reported 66% in Muhimbili, 70.1% in rural Tanzania and 84.5% in Mwanza (17)(18)(19). Our study ndings are also lower compared to a systematic review and meta-analysis of uncontrolled hypertension among patients with comorbidities in SSA which reported the prevalence ranging between 75.9% and 78.6% among patients with CKD (15) while the prevalence of uncontrolled hypertension among hypertensive adult patients in different parts of Ethiopia ranged from 48.0 % -56.7% (16, 20,32) which is lower to our study ndings. These differences could be accounted by variations in the studied populations; the other studies included also patients who had advanced CKD and they were conducted at are different geographical areas compared to Dodoma with different levels of urbanization.…”
Section: Discussioncontrasting
confidence: 67%
“…The prevalence of uncontrolled hypertension among patients with early CKD in our study was 58.3%, this is lower than ndings from other studies which reported 66% in Muhimbili, 70.1% in rural Tanzania and 84.5% in Mwanza (17)(18)(19). Our study ndings are also lower compared to a systematic review and meta-analysis of uncontrolled hypertension among patients with comorbidities in SSA which reported the prevalence ranging between 75.9% and 78.6% among patients with CKD (15) while the prevalence of uncontrolled hypertension among hypertensive adult patients in different parts of Ethiopia ranged from 48.0 % -56.7% (16, 20,32) which is lower to our study ndings. These differences could be accounted by variations in the studied populations; the other studies included also patients who had advanced CKD and they were conducted at are different geographical areas compared to Dodoma with different levels of urbanization.…”
Section: Discussioncontrasting
confidence: 67%
“…All self-care domains had acceptable reliability in previous studies in Ethiopia (7,15,54). The Cronbach's alpha of medication adherence, low salt, physical activity adherence, weight management, and alcohol use were 0.94, 0.74, 0.81, 0.93, and 0.92, respectively (22).…”
Section: Data Collection Procedures and Instrumentmentioning
confidence: 71%
“…Social support was adopted from the Oslo social support scale (OSSS-3) containing three items (57). The OSSS-3 has acceptable reliability with an alpha coe cient value of 0.86 in a previous study in Ethiopia (22). The patient's Medical chart was reviewed to retrieve clinical information (comorbidity status and Physical measurements (weight and height).…”
Section: Data Collection Procedures and Instrumentmentioning
confidence: 99%
See 2 more Smart Citations